A Nontraditional Instructional Model: Examining its Efficacy of Professional Development - Juthathip Kruanopphakhun; Dotan Nitzberg; Manami Hyoda (Canadian Society for Studies in Education, 2023)
The purpose of this study is to examine the efficacy of a nontraditional instructional model developed as a means of professional development, with multi-faceted theoretical and practical knowledge foundations. As the deliverables of the model, a training session and a web application were produced. In this study, the model was applied to 12 in-service teachers in a Canadian education context, using a quasi-experimental, convergent mixed-methods design. Quantitative data were collected with an evaluation questionnaire and analyzed by one sample t-test. Meanwhile, qualitative data were gathered from field notes and analyzed through the interpretive phenomenological analysis (IPA). The model was evaluated as an effective means to increase participants' teacher efficacy (t(10) = 1.81, P ≦ 0.001). Methodological limitations and recommendations were addressed. The model's external validity can be further investigated with its application to the wider audience.